The Effect of Workload and Wage Levels on Job Satisfaction of Honorary Employees with Motivation as a Mediation - Suwadi, Suwadi (Indonesia Academia Research Society, 2024)
Honorary staff members represent a significant component of Indonesia's current human resources, serving as an alternative workforce to support the performance of civil servants. Their presence is intended to address certain organizational needs. Job satisfaction is considered a crucial factor as it can impact organizational operations. It refers to employees’ supportive or unsupportive feelings towards their work or working conditions. This study investigated the influence of workload and wage levels on temporary employees' motivation and job satisfaction. The research employed quantitative methods utilizing Smart Partial Least Square (PLS) software version 3. The analysis comprises two sub-models: a measurement model (external model) and a structural model (internal model). A total of 94 respondents were selected using convenience sampling techniques. The findings revealed that workload significantly affects job satisfaction, mediated by motivation. Similarly, wage levels significantly impacted job satisfaction, with motivation as a mediating factor.